Sirex obesus (Hymenoptera: Siricidae) as invasive pest in pine plantations in Brazil - Carlos Frederico Wilcken; Thais Alves da Mota; Cláudia Helena de Oliveira; Vanessa Rafaela de Carvalho; Lucas Antonio Benso; Jessica Aparecida Gabia; Silvia Renata Siciliano Wilcken; Edson Luiz Furtado; Nathan M. Schiff; Mariane Bueno de Camargo; Murilo Fonseca Ribeiro (Scientific Reports)
Abstract The genus Sirex (Hymenoptera: Siricidae) consists of 29 species including the Sirex Woodwasp, Sirex noctilio, which is the main insect pest of pine plantations in the Southern Hemisphere including Brazil. In 2023, a species of Sirex similar to S. noctilio was discovered in Southeastern Brazil infesting pine plantations and causing tree mortality of up to 40%. We definitively identified this species as Sirex obesus based on both morphological characters and DNA barcodes. It is a species indigenous to the Southwestern United States and Northern and Central Mexico with little information available regarding its biology and control. This is the first record of S. obesus in Brazil and the first record of the species outside of North America. We document details about S. obesus occurrence in Brazil, describe preliminary damage caused in pine plantations and provide a partial list of natural enemies.